2009
DOI: 10.5194/hess-13-1867-2009
|View full text |Cite
|
Sign up to set email alerts
|

Catchment-scale non-linear groundwater-surface water interactions in densely drained lowland catchments

Abstract: Abstract. Freely discharging lowland catchments are characterized by a strongly seasonal contracting and expanding system of discharging streams and ditches. Due to this rapidly changing active channel network, discharge and solute transport cannot be modeled by a single characteristic travel path, travel time distribution, unit hydrograph, or linear reservoir. We propose a systematic spatial averaging approach to derive catchment-scale storage and discharge from point-scale water balances. The effects of spat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
68
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 26 publications
1
68
0
Order By: Relevance
“…Intensive agriculture in lowland catchments often leads to high nutrient losses and eutrophication of downstream waters (Oenema et al, 2007;Van der Molen, 1998;Vitousek et al, 2009). To identify effective measures to reduce these nutrient loads, the flow routes of water that enter a stream and their nutrient concentrations need to be quantified (Tiemeyer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Intensive agriculture in lowland catchments often leads to high nutrient losses and eutrophication of downstream waters (Oenema et al, 2007;Van der Molen, 1998;Vitousek et al, 2009). To identify effective measures to reduce these nutrient loads, the flow routes of water that enter a stream and their nutrient concentrations need to be quantified (Tiemeyer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many field-scale studies identified tube drain effluent as the major source of nitrate (Tiemeyer et al, 2006;Nangia et al, 2010;Rozemeijer et al, 2010c). However, the field scale at which these contributions can be directly measured (De Vos et al, 2000;Van der Velde et al, 2010a) often is not the scale of interest to water management authorities. Extrapolation of fields site results to entire catchments can easily lead to wrong conclusions as field sites can prove nonrepresentative of the patterns and processes that emerge at larger scales (Sivapalan, 2003;Soulsby et al, 2006;Didszun and Uhlenbrook, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations